AN ASSESSMENT OF THE IMPACT OF ENTREPRENEURSHIP STUDIES ON JOB CREATION AMONG GRADUATES OF GOMBE STATE UNIVERSITY - Shehu Hashidu, Mohammed; Adamu, Umar (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
In order to make Nigerian graduates self-reliant, the Nigerian universities commission (NUC) mandated the inclusion of entrepreneurial studies in the curriculum of all degree programs in Nigerian universities. Therefore, this paper examines the role this policy is playing in curbing unemployment in Nigeria. The study is Built on the theory of planned behaviour in which an ex ante and ex post survey was used to assess the impacts of elective and compulsory entrepreneurship education programs (EEPs) on students’ entrepreneurial intention and identification of opportunities. Data were collected by questionnaire from a sample of 367 participants in EEPs Gombe state university. Data were analysed using independent T-test to determine whether there is significant difference between pre and post. Both types of EEPs had significant positive impacts on students’ subjective norms and perceived behavioural control. Results also indicated that the elective EEPs significantly increased students’ entrepreneurial intention, although this increase was not significant for the compulsory EEPs. The findings contribute to the theory of planned behaviour and have implications for the design and delivery of EEPs.